Alternative Local Food Shopping Communities in Hungary - Izabella Bakos; Anikó Khademi-Vidra (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
As a result of concerns about the long-term sustainability of globalized retail trade and the stronger presence of health conscious consumer behaviour, governments and groups of conscious consumers worldwide are increasingly focusing on the promotion and development of local food systems and small-scale retail chains and the production of quality local food products to promote the market. In our paper, we would like to give an overview of community-led alternative types of local food systems, with particular attention to shopping community-type consumer and consumer communities. We also describe the main results of our primary research in the population and the shopping community. During the questionnaire we revealed general consumer behaviour and the demand and attitude of local food, the popularity of the customer communities in the settlement of the respondents. In the survey conducted among members of the consumer community, we looked at the analytical areas designated as a target in the population questionnaire for the purpose of comparability and our aim was to explore the sociometrics and lifestyles of communities as well as their community experiences and possible developments. Our hypothesis is that there is a close correlation between the respondents with higher education and income and the preferences of local food. Furthermore, it is assumed that there is a significant difference between the food consumption behaviors of the two samples examined.